2016
DOI: 10.1371/journal.pone.0156216
|View full text |Cite
|
Sign up to set email alerts
|

Mental Suffering in Protracted Political Conflict: Feeling Broken or Destroyed

Abstract: PurposeThis mixed-methods exploratory study identified and then developed and validated a quantitative measure of a new construct of mental suffering in the occupied Palestinian territory: feeling broken or destroyed.MethodsGroup interviews were conducted in 2011 with 68 Palestinians, most aged 30–40, in the West Bank, East Jerusalem, and the Gaza Strip to discern local definitions of functioning. Interview participants articulated of a type of suffering not captured in existing mental health instruments used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 50 publications
(52 reference statements)
3
18
0
Order By: Relevance
“…These findings provide support for studies (Barber et al, 2014; Barber, McNeely, Allen et al, 2016; Barber, McNeely, El Sarraj et al, 2016) that have similarly identified a unique type of existential form of mental suffering among Palestinians in the oPt linked to oppressive political and economic conditions. In addition, there was a marked absence of stability and safety due to the occupation, which adversely led to psychological and social suffering for participants (Barber et al, 2014).…”
Section: Findings and Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…These findings provide support for studies (Barber et al, 2014; Barber, McNeely, Allen et al, 2016; Barber, McNeely, El Sarraj et al, 2016) that have similarly identified a unique type of existential form of mental suffering among Palestinians in the oPt linked to oppressive political and economic conditions. In addition, there was a marked absence of stability and safety due to the occupation, which adversely led to psychological and social suffering for participants (Barber et al, 2014).…”
Section: Findings and Discussionsupporting
confidence: 74%
“…Consistent with Barber and colleagues' (Barber et al, 2014; Barber, McNeely, Allen et al, 2016; Barber, McNeely, El Sarraj et al, 2016) findings, aspects of existential mental suffering linked to oppressive political and economic conditions in the oPt were described in reference to one's spirit, morale, life and/or future as broken or destroyed; emotional and psychological exhaustion; and feeling tired. Suffering was described in reference to the self or spirit, morale and hopes and ambitions for the future, which was also found in this study.…”
Section: Findings and Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Given that muhattam could be reliably measured, the investigation emphasized the importance of using grounded and contextualized measures to assess the impact of political conflict on functioning (and health). 55 Muhattam was an important addition to the lexicon of idioms used by people to describe their health-where being well, afyeh in Arabic, is understood as a combination of physical, psychological, social, and emotional components that cannot be separated from each other. Such idioms not only form part of a health-disease continuum, but they are also used differently in different contexts so that sometimes they cannot be meaningfully (as opposed to semantically) translated into English using a single word.…”
Section: Developing New Measuresmentioning
confidence: 99%
“…A recent study of Palestinian wordings of distress concludes that in tandem with the conventional measurements of PTSD and depression, a representative, local expression of the consequences of living with the exhaustion of being occupied for years on end is “feeling broken” (Barber et al. ). This finding resonates with my attempt to think about how the pressure of the occupation and the obligation to keep fighting against it registers among the relatives who have to endure while their husbands and fathers fulfill this ideal…”
Section: Endurance In Palestine – Sumud and Sadnessmentioning
confidence: 99%